Differences in Diet Quality among Multiple US Racial/Ethnic Groups from the Mediators of Atherosclerosis in South Asians Living in America (MASALA) Study and the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 6 (4th March 2020) - Rodriguez, Luis A; Jin, Yichen; Talegawkar, Sameera A; Otto, Marcia C de Oliveira; Kandula, Namratha R; Herrington, David M; Kanaya, Alka M
ABSTRACT: Background: Diet quality is an important risk factor for type 2 diabetes (T2D) and cardiovascular disease (CVD). Little is known about the diet quality of South Asians in the United States, a group with higher rates of T2D and CVD compared with other racial/ethnic groups. Objective: This study determined whether diet quality differs between South Asian adults in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) Study and whites, Chinese Americans, African Americans, and Hispanics in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: Cross-sectional data from 3926 participants free of CVD from MESA visit 5 (2010–2011) and 889 South Asian participants from MASALA visit 1 (2010–2013) were pooled. Diet quality was assessed using the Alternative Healthy Eating Index (AHEI-2010) derived using FFQs. Multivariable linear regression models adjusted for age, sex, and total energy intake were used to compare mean differences in diet quality between the racial/ethnic groups. Results: MESA participants were, on average, 14 y older than MASALA participants. The adjusted mean (95% CI) scores for the AHEI-2010 were 70.2 (69.5, 70.9) among South Asians, 66.2 (66.3, 68.2) among Chinese Americans, 61.1 (60.7, 61.6) among whites, 59.0 (58.4, 59.7) among Hispanics, and 57.5 (56.9, 58.1) among African Americans. The mean AHEI scores among South Asians were 3.1 (1.8, 4.3), 9.2 (8.3, 10.1), 11.2 (10.2, 12.3), and 12.8 (11.8, 13.7) points higher compared with Chinese Americans, whites, Hispanics, and African Americans, respectively. Conclusions: South Asian adults in the United States have a higher diet quality compared with other racial/ethnic groups. This paradoxical finding is not consistent with the observed higher rates of T2D and CVD compared with other groups. This is further evidence of the importance of studying the South Asian population to better understand the causes of chronic disease not explained by diet quality.